Sistem Informasi Penjualan Pada Apotek Rizki Baturaja - Rusidi (Jurnal Informatika dan Komputer (JIK), 2022)
Rizki Drugstore in the field of selling drugs and medical equipment. In recording daily sales and purchases transaction, he have not used a system that can display reports automatically. This sales information system includes recording sales and purchases transaction, and automatically count of the stock of good. a method is used to analyze problems and design sales information system at Rizki Drugstore which will be implemented in the form of an application. The result of this research is a sales infomation system in Rizki Drugstore Baturaja. With this system, it is hoped that it will improve the performance of the sales staf